Understanding the paralinguistic features disclosure depicted in the lecturer’s visual modes of writing class instruction - Sumekto, Didik Rinan; Taufiqulloh, Taufiqulloh; Heny Setyawati; Siti Hikmah; Ghozali, Imam (Penerbit Universiti Kebangsaan Malaysia, 2021)
Today’s writing instruction performance is greatly aided by oral and nonverbal communication. This study intends to contextualize the lecturer’s visual modes regarding the paralinguistic features in writing class. Data were gathered from the PSETs’ self-rated questionnaire and the lecturer’s visual modes that were durably video recorded. Data were analysed using the IBM SPSS version 20 for descriptive and factor analysis, as well as the ELAN’s software to contextualize the non-verbal linguistic matters. The findings showed that the paralinguistic features, namely gesture, articulation, and loudness were strongly visible, whereas sonority and facial expression and lips setting were visible relating to the lecturer’s visual modes (r = .833, n = 243, p<.05). Meanwhile, Eigenvalue and factorial analysis affirmed two rooted paralinguistic features components of 83.803% (68.128% for component 1 and 15.675% for component 2). Further, ELAN analysis qualitatively contextualized the lecturer’s visual modes performance corresponding with the meta-discourse taxonomy through the portrait of the quoted material, dysfluencies, and discourse organization on introducing, delimiting, adding, and concluding the topic through the normative and pre-planned types of spoken data in the writing class activities. This study synchronizes the verbal and non-verbal viewpoints regarding both the PSETs and the lecturer’s understanding of the paralinguistic features in the writing class.